ANALISIS KANDUNGAN GIZI SELAI POH LEMBONGAN OLEH-OLEH LANGKA KHAS NUSA PENIDA - i wayan karta (Meditory : The Journal of Medical Laboratory, 2021)
Poh Lembongan mango is a typical mango from the island of Nusa Penida. During the harvest season the fruit is abundant and not used. The use of this mango fruit needs to be done research, so that it can be used as a souvenir product by processing it into jam. The purpose of this study was to analyze the nutritional content of the mango poh lembongan jam, and to test the organoleptic to determine the acceptability of the product as a souvenir.The research method used is descriptive, namely by laboratory tests and organoleptic tests. Laboratory tests were carried out by analyzing moisture content, ash content, fat content, protein content, carbohydrate content, and vitamin C. Organoleptic tests were carried out on the assessment of the aroma, taste, viscosity and acceptability parameters of 15 panelists.The results showed that the content of this jam was 19.649% water content; ash content 0.165%; fat content 0.573%; protein content of 0.907%, carbohydrate content of 78.705%, and vitamin C of 20.476%. Vitamin C which is quite high in jam gives the product the opportunity to be used as healthy food. Organoleptic tests show that the taste, aroma, texture can still be accepted by the community. Poh Lembongan mango jam has the potential to be developed into a typical souvenir product from Nusa Penida Island.